ANALISIS KETERAMPILAN MEMBACA DONGENG SISWA SEKOLAH DASAR SERTA RELEVANSINYA DENGAN PEMBELAJARAN MEMBACA - Akhmad Maksum (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2021)
Learning in elementary school is a fundamental foundation for conveying the planting of material correctly to students. Indonesian language learning in elementary schools expects students to have many language skills. One of them is the ability to read fairy tales. The aims of this study were (1) to describe the students' fairy tale reading skills (2) to describe the relevance of the students' fairy tale reading skills to learning to read. The methodology of this research is descriptive qualitative research. The subjects of this study were third grade students of SD Negeri 2 Baledono. While the object is the students' fairy tale reading skills and their relevance to learning to read. The data collection techniques used in this study were questionnaires, interviews, note-taking techniques, and document studies. Data analysis techniques using the Miles and Huberman model include data collection, data reduction, data presentation, and drawing conclusions or verification. The results of this study are very good (7.4%), good (48.1%), sufficient (40.7%), and need guidance (3.8%). An important finding in the study is the motivational factor in students that affects the enthusiasm for learning to read fairy tales in elementary school. In addition, the subject matter of reading fairy tales is considered to be quite difficult for students to master.